Innovation et développement dans les systèmes agricoles et alimentaires - Faure, Guy (éditions Quae, 2018)
Innovation is often touted as one of the key levers for promoting a more sustainable development. The book looks at innovation in the agri-food sector in light of today's major challenges by examining the different dimensions of the change and focusing on the meaning ascribed to innovation by the stakeholders. An understanding of the methods and systems for supporting the stakeholders who innovate provides professionals, politics, and civil society with useful and novel courses of action.